Melihat Arah Kemiskinan Nias Utara Dari Perspektif ADD, IPM serta PDRB - Yatatema Zai; Martin Luter Purba; Nancy Nopeline (CV. Ulil Albab Corp, 2024)
This study aims to analyze the causality of poverty in North Nias with the allocation of village funds, human development index and gross regional domestic product. The research method used is to use the Granger Causality Test. The data used is secondary data obtained from the Central Bureau of Statistics which consists of data on the number of poor people in North Nias in 2010-2023, the allocation of village funds in North Nias in 2010-2023, the Human Development Index of North Nias in 2010-2023 and the Gross Regional Domestic Product of North Nias in 2010-2023. This research was processed using Eviews version 10, but before processing, interpolation was carried out first to extend the research year due to data limitations. The results show that there is a causal relationship between poverty and ADD, there is no causal relationship between poverty and human development index, and there is no causal relationship between poverty and gross regional domestic product.